2013
DOI: 10.1101/gad.219105.113
|View full text |Cite
|
Sign up to set email alerts
|

Novel proteomic approach (PUNCH-P) reveals cell cycle-specific fluctuations in mRNA translation

Abstract: Monitoring protein synthesis is essential to our understanding of gene expression regulation, as protein abundance is thought to be predominantly controlled at the level of translation. Mass-spectrometric and RNA sequencing methods have been recently developed for investigating mRNA translation at a global level, but these still involve technical limitations and are not widely applicable. In this study, we describe a novel system-wide proteomic approach for direct monitoring of translation, termed puromycin-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(139 citation statements)
references
References 56 publications
(62 reference statements)
2
136
0
1
Order By: Relevance
“…For mammalian cells, both a computational study in 2010 and an experimental approach in 2011 concluded that “transcription is only half the story” 37 and protein-level regulation may be as important as that of the RNA-level 23, 38 . Similarly, in synchronized cells at different cell cycle stages, post-transcriptional regulation has been observed for much of the proteome 39 . However, these findings have been disputed, and reanalysis of the 2011 data showed that transcription may indeed do the majority of the regulatory workload, accounting for 56 to 81% of the overall variation in gene expression 40 .…”
Section: New Insights Into Gene Expression Regulationmentioning
confidence: 89%
“…For mammalian cells, both a computational study in 2010 and an experimental approach in 2011 concluded that “transcription is only half the story” 37 and protein-level regulation may be as important as that of the RNA-level 23, 38 . Similarly, in synchronized cells at different cell cycle stages, post-transcriptional regulation has been observed for much of the proteome 39 . However, these findings have been disputed, and reanalysis of the 2011 data showed that transcription may indeed do the majority of the regulatory workload, accounting for 56 to 81% of the overall variation in gene expression 40 .…”
Section: New Insights Into Gene Expression Regulationmentioning
confidence: 89%
“…, time point of rate change). This would require finer-resolution data, such as from ribosome profiling (49, 54, 55), puromycin-associated nascent chain proteomics (56), or combining pulsed-SILAC labeling with pulse-labeling using the methionine analogue azidohomoalanine (33, 57). Such enhanced methods will provide a framework to study the contributions of the protein life cycle in diverse dynamic systems and help identify new key regulators of these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our approach almost completely replaces endogenous eIF4G with a mutated variant at constant expression levels. Second, we assessed global translation by labeling with the translation elongation inhibitor puromycin (PMY [42]). Conventional metabolic labeling with Met analogs requires Met starvation, which elicits stress responses with effects on protein synthesis.…”
Section: Fig 3 Kinetic Analysis Of Mitotic Phosphorylation Of Eif4g(smentioning
confidence: 99%